KINERJA GURU PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN DILIHAT DARI KOMPETENSI PEDAGOGI, KEPRIBADIAN, SOSIAL DAN PROFESIONAL - damrah, damrah; pitnawati, pitnawati; rozi, fahrur; erianti, erianti; astuti, yuni (Jurnal Ilmu Keolahragaan Undiksha, 2020)
This study aims to determine the performance of the Physical and Sports Physical Education teacher at MTsS Nurul Iman Dharmasraya Regency based on pedagogic, personality, social and professional competence.The research method used is qualitative. The informants in this study were the principal, teachers, school supervisors, the community, and students. Data were obtained by observation, interview and documentation techniques. And data analysis techniques used are using triangulation.  The results showed that: 1) Based on the Pedagogic performance of Physical and Sports Physical Education Teachers in Nurul Iman Private Madrasah Stanawiyah categorized as not good. 2) Based on personality, the performance of the Physical and Physical Education Teachers in Madrasah Stanawiyah Private Nurul Iman is categorized as good. 3) Based on social competence, theperformance of Physical and Sports Physical Education Teachers in the Private Nurawi Iman Madrasah Stanawiyah is categorized as not good. 4) Based on the professional competence the performance of the Physical and Physical Education Teachers in the Madrasah Stanawiyah Private Nurul Iman in professional competencies is categorized as not good.